Doggolingo and first language acquisition: Morphosyntactic Analysis of Doggolingo memes - Aguilar Pérez, Carla Alejandra (2019)
Computer mediated communication (CMC) has started to shape the way language is used to communicate. It has also contributed to the creation of internet dialects. This research focuses on the morphosyntactical features of one internet dialect known as doggolingo, which displays certain deviations from Standard English. Doggolingo is defined as the caption that is embedded in funny images of dogs, widely known as memes. The present paper analyzes a selected corpus collected from a google search. The analysis is based on three aspects: function words omission (articles and subject omission), ellipsis (copula omission), and phoneme/grapheme correspondence known as eye dialect. The results show that doggolingo shares similarities mainly with two stages of first language acquisition as well as a tendency for vowel changing. Two possible types of doggolingo are also discussed.